Strengthening the development of safety and health guidelines during post COVID-19 condition for construction site project / Siti Hamidah Abdull Rahman … [et al.] - Abdull Rahman, Siti Hamidah; Kamaruding, Musmuliadi; Mohd Nusa, Fatin Najwa; Mohd Dzulkifli, Syahrun Neizam (2022)
COVID-19 has had a significant impact on the construction industry, and it is critical that the economy recovers quickly after COVID-19. Construction project jobsite safety and health, as well as timely project delivery, must be strictly always adhered to. The aim of this research is to identify the understanding, acceptance, and feasibility of the new safety and health guidelines application, as well as to determine the level of knowledge in the senior management of a construction company about the new performance safety and health guidelines due to the COVID-19 pandemic condition, by examining the new safety and health application guidance for the post-COVID-19 situation in the project jobsite. The questionnaire survey (quantitative approach) was distributed to construction sites in Klang Valley. Stratified random sampling was used to obtain data from Grade 7 contractor companies. A total of 140 questionnaires were distributed, with 50 received and analysed using descriptive and frequency analysis, as well as the Relative Importance Index (RII). As a result, the most significant new safety and health guidelines applications in construction sites are the implementation of health screening procedures, the establishment of a recording logbook, and temperature screening at the entry point using a touchless thermometer. One of the most significant aspects of the new safety and health guidelines application’s acceptance and feasibility is the routine cleaning and disinfection of commonly touched surfaces, site offices, and labour dormitories every two hours, four times a day. Lastly, the top management and are encouraged to have individual discussions with employees about the precautions and considerations for those with health problems returning to work, as well as precautions to make the workplace safe. This study complements and benefits clients, contractors, project managers, and other project participants by providing an understanding of the existing implementation of safety and health guidelines application during post-COVID19 conditions for construction site projects.